2015
DOI: 10.1152/ajprenal.00278.2014
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation induces mitochondrial uncoupling, increased kidney oxygen consumption, and decreased kidney oxygen tension

Abstract: Hypoxia is an acknowledged pathway to renal injury and ischemia-reperfusion (I/R) and is known to reduce renal oxygen tension (Po2). We hypothesized that renal I/R increases oxidative damage and induces mitochondrial uncoupling, resulting in increased oxygen consumption and hence kidney hypoxia. Lewis rats underwent syngenic renal transplantation (TX) and contralateral nephrectomy. Controls were uninephrectomized (1K-CON) or left untreated (2K-CON). After 7 days, urinary excretion of protein and thiobarbituric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Indeed it was demonstrated in experimental diabetes that hypoxia had occurred at an early stage (dos Santos et al, 2007) before any histologic damage could be observed (Manotham et al, 2004). This has also been observed in experimental kidney transplantation (Papazova et al, 2015). Moreover, hypoxia-inducible factor-1alpha has been immunohistochemically detected in kidney allografts with (sub)clinical rejection at 3 months after transplantation and beyond (Rosenberger et al, 2007).…”
Section: Conventional Vs Functional Mri For the Assessment Of Subclisupporting
confidence: 65%
“…Indeed it was demonstrated in experimental diabetes that hypoxia had occurred at an early stage (dos Santos et al, 2007) before any histologic damage could be observed (Manotham et al, 2004). This has also been observed in experimental kidney transplantation (Papazova et al, 2015). Moreover, hypoxia-inducible factor-1alpha has been immunohistochemically detected in kidney allografts with (sub)clinical rejection at 3 months after transplantation and beyond (Rosenberger et al, 2007).…”
Section: Conventional Vs Functional Mri For the Assessment Of Subclisupporting
confidence: 65%
“…Renal oxygen delivery (DnormalO2) was calculated as the product of RBF and arterial O 2 ct, while renal oxygen consumption (QnormalO2) was calculated as the product of RBF and the difference between arterial and renal venous blood oxygen content (Papazova et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…In kidney transplantation, hypoxia is a critical factor affecting the development of renal damage during the transplant process from donor to recipient. 8,12 Hypoxia is also believed to play a key role in both acute and chronic kidney diseases and in the transition from acute to chronic kidney diseases. 38 In fact, it is thought that hypoxia plays a major Relative quantitation of phosphorylated ERK1/2 (P-ERK1/2)/total ERK1/2 (T-ERK1/2).…”
Section: Discussionmentioning
confidence: 99%
“…7 Hypoxia is also an acknowledged pathway to renal injury and ischemiareperfusion, which is an inevitable event accompanying renal transplantation and is considered a common cause for delayed graft function and acute renal failure. [8][9][10][11] Understanding the mechanisms involved in hypoxic pathophysiology is of great importance for the prevention and treatment of hypoxic renal injury, especially for improving renal allograft outcome in the recipient after kidney transplantation. 12 Hypoxia can activate a large range of signaling networks and regulate the expression of a variety of growth factors, cytokines, and signaling molecules in a cell-and tissue-specific manner.…”
Section: Introductionmentioning
confidence: 99%